Anxiety and Depression in Health Workers and General Population During COVID‐19 in IRAN: A Cross‐Sectional Study. Issue 1 (25th December 2020) - Hassannia, Leila; Taghizadeh, Fatemeh; Moosazadeh, Mahmood; Zarghami, Mehran; Taghizadeh, Hassan; Dooki, Azadeh Fathi; Fathi, Mohammad; Alizadeh‐Navaei, Reza; Hedayatizadeh‐Omran, Akbar; Dehghan, Niloufar
Abstract: Background: The COVID‐19 outbreak has exerted a great deal of psychological pressure on Iranian health workers and the general population. The aim of this study was to determine the effect of pandemic on anxiety and depression in Iranian population. Methods: An online cross‐sectional study was conducted for the general public and healthcare workers in Iran using a questionnaire comprised of demographic questions and Hospital Anxiety and Depression Scale. Chi‐square test and univariate and multivariate logistic regression models were conducted. Results: Of the 2045 participants, 1136 (65.6%) were considered to have moderate and severe anxiety symptoms, and 865 (42.3%) had moderate and severe depression symptoms. The prevalence of anxiety was higher in the females than in the males (OR = 1.4, 95% CI: 1.123‐1.643, P = .002); the prevalence of anxiety was significantly higher in those aged 30‐39 years than in other age‐groups (OR = 1.6, 95% CI: 1.123‐2.320, P = .001); furthermore, the prevalence of anxiety and depression was significantly higher in doctors and nurses compared with other occupations ((OR = 1.9, 95% CI: 1.367‐2.491, P < .001) and (OR = 1.5, 95% CI: 1.154‐2.021, P = .003)). In addition, the prevalence of anxiety symptoms in the likely infected COVID‐19 group was higher than in the noninfected COVID‐19 group (OR = 1.35, 95% CI: 1.093‐1.654, P = .005). Conclusions: Regarding the high prevalence of anxiety and depression symptoms, especially among healthcare workers, appropriate psychological/psychiatric intervention necessitates. Abstract : An online cross‐sectional study was conducted for the general public and healthcare workers in Iran using a questionnaire comprised of demographic questions and Hospital Anxiety and Depression Scale. Regarding the high prevalence of anxiety and depression symptoms, especially among healthcare workers, appropriate psychological/psychiatric intervention necessitates.